Incidence and risk factors for gangrene in patients with systemic sclerosis from the EUSTAR cohort. (2nd December 2019) - Mihai, Carina; Distler, Oliver; Gheorghiu, Ana Maria; Constantin, Paul I; Dobrota, Rucsandra; Jordan, Suzana; Smith, Vanessa; Hachulla, Eric; Henes, Jörg; Siegert, Elise; Vettori, Serena; Müller-Ladner, Ulf; et al.
Abstract: Objective: In patients with SSc, peripheral vasculopathy can promote critical ischaemia and gangrene. The aim of this study was to investigate the prevalence, incidence and risk factors for gangrene in the EUSTAR cohort. Methods: We included patients from the EUSTAR database fulfilling the ACR 1980 or the ACR/EULAR 2013 classification criteria for SSc, with at least one visit recording data on gangrene. Centres were asked for supplementary data on traditional cardiovascular risk factors. We analysed the cross-sectional relationship between gangrene and its potential risk factors by univariable and multivariable logistic regression. Longitudinal data were analysed by Cox proportional hazards regression. Results: 1757 patients were analysed (age 55.9 [14.5] years, disease duration 7.9 [10.3] years, male sex 16.7%, 24.6% diffuse cutaneous subset [dcSSc]). At inclusion, 8.9% of patients had current or previous digital gangrene, 16.1% had current digital ulcers (DUs) and 42.7% had ever had DUs (current or previous). Older age, DUs ever and dcSSc were statistically significant risk factors for gangrene in the cross-sectional multivariable model. During a median follow-up of 13.1 months, 16/771 (0.9%) patients developed gangrene. All 16 patients who developed gangrene had previously had DUs and gangrene. Further risk factors for incident gangrene were the dcSSc subset and longer disease duration. Conclusion: In unselected SSc patients, gangrene occurs in about 9% of SSc patients. DUs ever and, to a lesser extent, the dcSSc subset are strongly and independently associated with gangrene, while traditional cardiovascular risk factors could not be identified as risk factors.